Pengaruh Konsentrasi Stimulan dan Intensitas Sadap pada Produksi Lateks Tanaman Karet Seedling (Hevea brasiliensis Muell. Arg.) - Charles Muhtaria; Dedi Supriyatdi; Muhammad Rofiq (Jurnal Agro Industri Perkebunan, 2015)
The lacks of national latex productivity caused by most of rubber trees (85%)managed by folks plantations which have low productivities. Good management and performance of cultivation needs for increase latex productivity, mainly in tapping process. The purpose of this research was to study about effects of ethepon stimulant application on seedling rubber trees,determine the proper tapping intensity, and to find out interaction between stimulant applications with tapping intensitytowards seedling rubber trees.The study have been done during 3 months from September to November 2014 using Randomized Complete Block Design (RCBD) factorial with 2 factor. The first factor wasstimulant concentration (C) with 2 stage, C0 = without stimulant application and C1 = stimulant application as recommended rate. The second factor wastapping intensity (I) with 3 stage. I1= once every two days, I2= once every 3 days, and I3= once every 4 days.Thus obtained 6 treatment combinationwith 4 repeats. The study result shows that the latex and dry rubber production towards seedling rubber trees could be increased by stimulant application, tapping intensity did not give effect on increasing latex volume and dry rubber production, and there is no interaction between stimulant applications with tapping intensity.Keywords: latex production, seedling rubber trees,stimulant, tapping intensityPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/19